2016
DOI: 10.19173/irrodl.v17i1.2111
|View full text |Cite
|
Sign up to set email alerts
|

An Empirical Study of Factors Affecting Mobile Wireless Technology Adoption for Promoting Interactive Lectures in Higher Education

Abstract: Use of mobile technology is widespread, particularly among the younger generation. There is a huge potential for utilizing such technology in lecture classes with large numbers of students, serving as an interaction tool between the students and lecturers. The challenge is to identify significant adoption factors to ensure effective adoption of mobile technology to promote interactivity between students and lecturers. This paper aims to examine factors supporting the use of mobile wireless technology during le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
17
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 76 publications
5
17
0
Order By: Relevance
“…This research found that information quality and system quality had some influence on the intention to use the ClassStart. The results of this study are consistent with previous research, which confirmed that system and information quality were important indicators for the adoption of user technology (Gan & Balakrishnan, 2016). In developing countries such as Oman, Al-Busaidi (2013) and Sharma et al (2017) found that the main issue affecting the acceptance of learners was system quality.…”
Section: General Discussion and Theoretical Implicationssupporting
confidence: 90%
“…This research found that information quality and system quality had some influence on the intention to use the ClassStart. The results of this study are consistent with previous research, which confirmed that system and information quality were important indicators for the adoption of user technology (Gan & Balakrishnan, 2016). In developing countries such as Oman, Al-Busaidi (2013) and Sharma et al (2017) found that the main issue affecting the acceptance of learners was system quality.…”
Section: General Discussion and Theoretical Implicationssupporting
confidence: 90%
“…Like recent mobile learning studies in higher education (Biddix et al, ; Davison & Lazaros, ; Gan & Balakrishnan, ), the results of this study with 189 students show that higher education students utilise a range of technologies including laptops, smartphones, desktop computers, tablets, mobile phones and MP3 players. Utilisation of laptops was predictably high (especially by Australian students).…”
Section: Discussion Of Findingssupporting
confidence: 78%
“…Technology Acceptance Model (TAM) by Davis (1989) is extensively studied and adopted for its simplicity and predictive accuracy in the field of technology acceptance. TAM model has been expanded by numerous researchers and has been applied in various technologies including mobile banking (Lule et al., 2012), e-learning (Cheung and Vogel, 2013; Chow et al., 2012), teleconferencing (Park et al., 2014b), short message service (Muk and Chung, 2015), e-government (Hamid et al., 2016; Lin et al., 2011), mobile learning (Park et al., 2012; Gan and Balakrishnan, 2016, 2017, 2018), etc.…”
Section: Introductionmentioning
confidence: 99%
“…Enjoyment is always portrayed as one of the intrinsic motivations that drives people to do something because they enjoy doing it. Multiple studies revealed that enjoyment as intrinsic motivator is one of the significant factors in predicting continuance intention and acceptance of IT technology (Gan and Balakrishnan, 2016, 2017; Park et al., 2014a; Teo and Noyes, 2011; Venkatesh, 2000; Wang et al., 2013; Wu and Gao, 2011; Yi and Hwang, 2003; Zhang et al., 2008). It is evidence that people will be willing to spend more time and effort on a task and have increased explanatory behaviour and greater acceptance of information technology when tasks create a high level of enjoyment.…”
Section: Introductionmentioning
confidence: 99%